Kesulitan Siswa dalam Menyelesaikan Soal-Soal Pisa pada Konten Change And Relationship Level 4, 5, dan 6 di SMP N 1 Indralaya - Simalango, Maria Mareta; Darmawijoyo; Aisyah, Nyimas (Mathematics Education Journal, 2018)
This research has a purpose to know the student’s difficulties in resolving PISA problems in Change and Relationship content for level 4, 5, and 6 in Junior High School. This is a descriptive research that has a purpose to identify and describe the student’s difficulties in resolving PISA problems in Change and Relationship content for level 4, 5, and 6. The subject of this research are 6 students of IX grade of SMP Negeri 1 Inderalaya. This research used data gathering technique that are written test and interview. The results of this research showed that students resolving PISA problems in Change and Relationship content for level 4, 5, and 6 felt difficult in understanding the problems, transforming real world problems into mathematics structure, solving the mathematics problem and interpreting mathematics solutions into the real world. The results show the difficulty in understanding the problem and transforming real world problems into mathematics structure is more dominant than the other difficulties.